Emotion Introduction Program "Senia" (Non-Verbal Expression and Interaction Art for Activities) for ODGJ Patients tt Rskd Dadi in the City of Makassar - Kartika Cahyaningrum; Fatima Az-Zahra; Zalsah Nabila Ananda; Nur Jumira; Andi Muhammad Hijril Razak (Jurnal Pengabdian Masyarakat Bestari, 2023)
People with mental disorders, especially schizophrenia, struggle to recognize and manage their emotions. Therefore, community-based rehabilitation programs like SENIA are necessary to help them develop an understanding of emotions, emotional expression, and empathy. This program involves activities such as emotion recognition, emotion identification through card games, practicing emotion recognition with pictures, and education on healthy emotional expression. The results of the first stage show patient participation, the second stage indicates improvement in their ability to identify and narrate emotions, and the third stage involves patients in expressing emotions healthily under expert guidance. Although the program is running well, there is a need to consider the development of programs that involve more individuals comprehensively and maximally.